The Impact of Innovation Orientation on Business Performance - Krzysztof BORODAKO; Jadwiga BERBEKA; Michal RUDNICKI; Mariusz LAPCZYNSKI (Communications of International Proceedings, 2021)
Innovation orientation (IO) plays an important role in knowledge creation and transfer. The implementation of IO in different types of business services seems to be under-researched. A literature review confirmed the lack of empirical research on IO in various types of knowledge-intensive business services and its impact on business performance. We propose a six-dimensional construct of IO, including the dimensions of strategy, organizational culture, human resources, structural-process, market and technology. The empirical research was based on 1,500 questionnaires. To ensure a high level of scientific accuracy, the convergent and discriminant validity were assessed during the first step of the analyses. The results confirm that the level of IO differs among the researched types of business services, so service type can be treated as a moderator of the impact of IO on business performance. The results indicated that some dimensions had a higher significance on this relationship. Our study contributes to the current state of knowledge by introducing the six-dimensional construct of innovation orientation and deepens our understanding of the impact of business services type on the relationship between innovation orientation and business performance.
Keywords: Innovation Orientation; Knowledge; Business Services; Strategy.